Aplikasi Digital untuk Mendukung Penanggulangan Stunting dalam Lingkup Kegiatan Academic Health System (AHS) - Sukirno, Sukirno (Media Informasi, 2024)
Stunting is a national health problem and has become an issue and concern for all parties. Stunting is chronic malnutrition characterized by a short body. Stunting sufferers are generally vulnerable to disease, have low intelligence levels, and have low productivity. The government's efforts to prevent stunting include making Presidential Regulation llllllll72 of 2021 concerning the acceleration of stunting reduction. Academic Health System (AHS) Faculty of Medicine, Public Health, and Nursing (FK-KMK) Universitas Gadjah Mada participates in supporting the stunting reduction program. Stunting is one of the priority program themes of the Academic Health System. The purpose of writing this article is to explain the development of eLib FKKMK as an application to integrate stunting information sources to support the activities of the AHS FK-KMK UGM network. eLib FKKMK is a digital platform application containing a collection of books, audiobooks, and videos with stunting. eLib FKKMK can be accessed using the latest Android, PC, or iOS technology. Users within the AHS network can easily use eLib FKKMK—the addition of stunting content increases in the number of books, audiobooks, and videos. eLib FKKMK can provide a source of stunting information that can reduce stunting in the AHS FKKMK UGM network hospital. Socialization or promotion activities for library users at the AHS FK-KMK UGM network 7 hospitals should always be carried out so that many can use the eLib.